Study on Europium-Doped Hydroxyapatite Nanoparticles by Fourier Transform Infrared Spectroscopy and Their Antimicrobial Properties - Simona-Liliana Iconaru; Mikael Motelica-Heino; Daniela Predoi (Journal of Spectroscopy)
Fourier transform infrared spectroscopy (FT-IR) analysis was conducted on europium-doped hydroxyapatite, Ca10-xEux(PO4)6(OH)2 nanocrystalline powders (Eu:HAp) with 0≤xEu≤0.2. Antimicrobial studies were also performed for the first time on Eu:HAp. The antimicrobial properties of Eu:HAp nanoparticles with 0≤xEu≤0.2 on Gram-negative (E. coli ATCC 25922, Pseudomonas aeruginosa 1397) and Gram-positive (Staphylococcus aureus 0364, Enterococcus faecalis ATCC 29212) bacteria systems and a species of fungus (Candida albicans ATCC 10231) were reported. Our study demonstrates that the antimicrobial activity of Eu:HAp nanoparticles is dependent on the europium concentration.